Family Role, Experiences Exposure, and Entrepreneurial Judgment Skills Toward Start-Up Entrepreneurs’ Productivity - Silvy Saunia; Nur Hidayah (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to analyze and explain the empirical influences of role of family, experiences exposure, and entrepreneurial judgment skills, eachly toward entrepreneurs’ productivity. This study applies descriptive research design, quanitatively obtained, and analyzed statistically. The data are collected from 40 individuals, entrepreneurs who establish or manage start-up in Indonesia, as sample. Technique used to select the sample is by non-probability sampling, where the instrument used to evaluate four variable is questionnaire through Google-form, to collect data. Respondent’s feedbacks are then assessed through SmartPLS 3.0 software. Three independent variables simultaneously able to influence dependent variable moderately. In hypotheses testing, role of family positively and insignificantly influences entrepreneurs’ productivity, while experiences exposure, entrepreneurial judgment skills positively and significantly influence entrepreneurs’ productivity.